1972
DOI: 10.1021/jm00276a021
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase reactivators. Pyridyl and anilyl trifluoromethyl ketoximes

Abstract: 67 (1971). (17) Edinburgh Staff, "Pharmacological Experiments on Isolated Preparations," 1st ed, Livingstone, Edinburgh, pp 13-63. (18) G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Salvador et al [68] have synthesized 2-, 3-, and 4-trifluoromethyl ketoxime isomers (13) of pyridine and N,N-dimethylaniline. They found that these nucleophiles were quite active in providing protection against either paraoxon or sarin.…”
Section: Nucleophilicity Of Oximate Ions In Water and Cationic Micellesmentioning
confidence: 99%
“…Salvador et al [68] have synthesized 2-, 3-, and 4-trifluoromethyl ketoxime isomers (13) of pyridine and N,N-dimethylaniline. They found that these nucleophiles were quite active in providing protection against either paraoxon or sarin.…”
Section: Nucleophilicity Of Oximate Ions In Water and Cationic Micellesmentioning
confidence: 99%
“…19 syn-Benzaldoxime (BAO) (Aldrich) was used as received. ␣,␣,␣-Trifluoroacetophenone oxime (TFAO) was prepared as described by Salvador et al 20 and was an equimolar synanti mixture. 21a 2-Methoxybenzaldoxime (BAO-OMe) was prepared as described 22 and was recrystallized from EtOH, m.p.…”
Section: Methodsmentioning
confidence: 99%
“…Acid dissociation constants for pyridinealdoximes and their methiodides (2-, 3-and 4-PAM) [28][29][30][31][32][33] reflect the inductive and conjugative effect of the nitrogen atom. Reactivating power of inhibited enzyme decreases in the order 2-PAM (pK a 7.8) > 4-PAM (8.5) ) 3-PAM (9.2) [33,34].We measured pK a values and secondorder rate constants (k ox À) towards sarin of the fluorinated pyridine aldoximes and some perprotio analogues (Table 1). A fluorine atom in the 3-position barely affected the pK a of pyridine 2-and 4-aldoxime.…”
Section: Porton Screening Datamentioning
confidence: 99%